THE RELATIONSHIP OF FIRE INCIDENT AND AREA VULNERABILITY: CASE STUDY OF WEST JAKARTA MUNICIPALITY, INDONESIA - Nugraha, Fajar; Lestari, Fatma; Semedi, Jarot Mulyo; Rahatiningtyas, Nurul Sri; Wibowo, Andrio A. (Jurnal Geografi Lingkungan Tropik (Journal of Geography of Tropical Environments), 2022)
Fire incident has a great impact on the loss of lives and financial loss due to property damage. Areas with high population density, densely physical building conditions, and irregular building patterns commonly form congested residential slum areas are vulnerable to fire hazards. The capital city of Jakarta is the most populous city in Indonesia and the most densely populated city, with an average of 15,900 people per sq km. In 2019, there was 2,109 fire incident recorded, and nearly 20% of them occurred within the West Jakarta Municipality area. This study investigates the relationship of population density and building density, which are considered vulnerability factors of an area, to fire incidents within the West Jakarta Municipality area in 2019. This study investigates 56 villages within the eight subdistricts of West Jakarta Municipality. This study is an ecologic study, and the bivariate test used is Spearman's rank correlation. The fire incident was significantly correlated with the building density (p-value=0,0001; r=-0,533) and the population density (p-value=0,04; r=-0,276). The distribution of densely populated and high building density villages is dominant in West Jakarta Municipality's east region. In contrast, the villages with high fire incident are dominant in West Jakarta Municipality's west region.